Reinsurance Transactions and Gross Premium Income of Non-Life Insurance Companies in Nigeria: An ARDL Approach - Fadun, Olajide Solomon; Aduloju, Sunday Adekunle; Oluwaleye, Taiwo Olarinre (The Journal of Accounting and Management, 2023)
The study examined the relationship between reinsurance premiums ceded and gross premium income and the effect of reinsurance premium accepted on the gross premium income of Nigerian non-life insurance providers. This study is a longitudinal research design. We engaged secondary data extracted from the Nigeria Insurance Association (NIA) Digest’s report for all the non-life insurers within the period of 2007-2021. Data obtained was analysed using descriptive statistics and Auto Regressive Distributed Lag (ARDL). The results revealed that reinsurance premium ceded has a positive significant relationship with gross premium income, and reinsurance premium accepted has a positive significant effect on gross premium income of Nigerian non-life insurance providers. It was also confirmed that reinsurance premium ceded and reinsurance premium accepted have a short and long-run effect on the gross premium income of Nigerian non-life insurance providers. Consequently, this study established that reinsurance transactions have a positive significant effect on the gross premium income of Nigerian non-life insurance firms. Therefore, this study recommends among others that Nigerian non-life insurance providers should improve their underwriting capacity especially for high-risk sectors like oil and gas, marine and aviation as well as other sectors to increase their gross premium income.